Implementation of the Qiraah Jahriyyah Strategy in Improving Maharah Qiraah Learning at IAI Sunan Kalijogo Malang - Maliyanah, Alya Afifah; Fitriani, Laily (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Reading skills in learning Arabic are very important to pay attention to because they are part of the importance of understanding Arabic. With reading skills, someone who learns Arabic will know what reading is good and correct according to the rules and will know the meaning of Arabic reading. This article aims to (1) find out the application of the qiraah jahriyyah strategy in learning Arabic at IAI SKJ Malang (2) find out the difficulties in applying the qiraah jahriyyah strategy in learning Arabic at IAI SKJ Malang and solutions in applying the qiraah jahriyyah strategy to learning Arabic at IAI SKJ Malang. This research is qualitative research based on field studies, data was collected through observation, interviews and documentation techniques. In this case, the researcher made direct observations at IAI SKJ Malang and interviewed teachers who taught Arabic language courses, especially in the Arabic Language Education department, semester 3. The results of this research were that the implementation of the qiraah jahriyyah strategy was very good and created positive things for the students, However, there are problems from several factors, namely (1) internal factors, errors in sound system, punctuation and recitation. (2) external factors, resulting from student factors and learning media factors. And the solution is the activeness of a teacher and student which is very important in improving Arabic language learning.